If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(20 + -1n) = 4 (20 * 4 + -1n * 4) = 4 (80 + -4n) = 4 Solving 80 + -4n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + -4n = 4 + -80 Combine like terms: 80 + -80 = 0 0 + -4n = 4 + -80 -4n = 4 + -80 Combine like terms: 4 + -80 = -76 -4n = -76 Divide each side by '-4'. n = 19 Simplifying n = 19
| x^2+5-3x=0 | | 15k-3=4+6k | | 12x=4(7+24) | | 20a^2+5a=0 | | -12x=4(7+24) | | 2+2x=x+14 | | 8=3(3c+5) | | 16k+35= | | 5(n+1)+10=20 | | 6y-3=6y+18 | | 3x+4=x+24 | | -22=7(1+3v)-8 | | .5a-9=4a+5 | | 5(n+2)=30 | | 5g-15=3(-5) | | 0.02+0.01=0.005 | | 2(10-n)=6 | | -5a+2a= | | 5(1+7a)-2a=38 | | 4x+1=20x-47 | | 4(n-1)=20 | | -7d+6=-12 | | 5+5=a | | -7+6=-12 | | 3(n+1)=20 | | 3(2x+7)=57 | | 1y-5=y+9 | | 20-3n=14 | | -5(p-7)+3p=21 | | -5(9+4x)=-45 | | 15=-11-2k | | -0.6(6x-27)=-4 |